The SELFIE framework for integrated care for multi-morbidity: Development and description - Leijten, Fenna R.M.; Struckmann, Verena; van Ginneken, Ewout; Czypionka, Thomas; Kraus, Markus; Reiss, Miriam; Tsiachristas, Apostolos; Boland, Melinde; de Bont, Antoinette; Bal, Roland; Busse, Reinhard; Rutten-van Mölken, Maureen (Health policy (Amsterdam), 2018)
•A framework for integrated care for multi-morbidity is presented.•A holistic understanding of the individual is at the core of the framework.•Concepts are structured according to the six WHO key components of health systems.•The framework can be used by different stakeholders in different contexts.•The framework can guide the description and evaluation of integrated care for multi-morbidity. The rise of multi-morbidity constitutes a serious challenge in health and social care organisation that requires a shift from disease- towards person-centred integrated care. The aim of the current study was to develop a conceptual framework that can aid the development, implementation, description, and evaluation of integrated care programmes for multi-morbidity. A scoping review and expert discussions were used to identify and structure concepts for integrated care for multi-morbidity. A search of scientific and grey literature was conducted. meetings were organised within the SELFIE research project with representatives of five stakeholder groups (5Ps): patients, partners, professionals, payers, and policy makers. In the scientific literature 11,641 publications were identified, 92 were included for data extraction. A draft framework was constructed that was adapted after discussion with SELFIE partners from 8 EU countries and 5P representatives. The core of the framework is the holistic understanding of the person with multi-morbidity in his or her environment. Around the core, concepts were grouped into adapted WHO components of health systems: service delivery, leadership & governance, workforce, financing, technologies & medical products, and information & research. Within each component micro, meso, and macro levels are distinguished. The framework structures relevant concepts in integrated care for multi-morbidity and can be applied by different stakeholders to guide development, implementation, description, and evaluation.